KRAB zinc-finger proteins regulate endogenous retroviruses to sculpt germline transcriptomes and genome evolution - Otsuka, Kai; Sakashita, Akihiko; Maezawa, So; Schultz, Richard M.; Namekawa, Satoshi H. (Genome Research, 2025)
As transposable elements (TEs) coevolved with the host genome, the host genome exploited TEs as functional regulatory elements of gene expression. Here we show that a subset of KRAB domain–containing zinc-finger proteins (KZFPs), which are highly expressed in mitotically dividing spermatogonia, repress the enhancer function of endogenous retroviruses (ERVs) and that the release from KZFP-mediated repression allows activation of ERV enhancers upon entry into meiosis. This regulatory feature is observed for independently evolved KZFPs and ERVs in mice and humans, suggesting evolutionary conservation in mammals. Further, we show that KZFP-targeted ERVs are underrepresented on the sex chromosomes in meiosis, suggesting that meiotic sex chromosome inactivation (MSCI) may antagonize the coevolution of KZFPs and ERVs in mammals. Our study uncovers a mechanism by which a subset of KZFPs regulate ERVs to sculpt germline transcriptomes. We propose that epigenetic programming during the transition from mitotic spermatogonia to meiotic spermatocytes facilitates the coevolution of KZFPs and TEs on autosomes and is antagonized by MSCI.